Equilibrium in Ethic Economics - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
We will study the concept of equilibrium in conventional and ethic economics in this paper. By a general review of the subject of equilibrium from basic sciences' point of view, we will study the meaning of equilibrium at different levels of micro, macro, and international economics; and by considering the lust and anger powers of human being, the concept of optimizing human behavior in Neoclassical theory will be studied. The hypothesis of “rational behavior” and philosophical and the root of thoughts and human behavior modeling in neoclassical economics will be analyzed from pleasure or utilitarianism-based point of view. By putting forward the concept of “perfection” as materializing innate power of creatures, we introduce the concept of ethic science so that we will review the correctness and goodness of actions and qualities of the human being in the process of optimizing economic behavior. Level of equilibrium in the powers as prescribed by ethic science with the meaning of preventing overindulgence and under-indulgence will be discussed. The meaning of equilibrium in ethic economics is a global optimum and in the form of utility point of view, has a broader domain of qualities and intellectualities and human being spirituals always at least is in a position that is better than Neoclassical optimized behavior (which is a local optimum).Some qualities related to economic behavior and overindulgence and under-indulgence and their equilibrium have also been considered. Equilibrium in ethic economics means using resources and locating everything in its right position and in the direction of obtaining human being perfection. Putting things in their right position is the optimal use of them from a mathematical point of view, and perfection is defined as reaching the ultimate innate of every creature. This means that in order to maximize the utility, resources should be used in a manner that in addition to ensuring human being material needs, assure the necessary background for maximizing mental and spiritual growth and elevation of him. DOI: https://doi.org/10.5281/zenodo.3402335